The Effect of NPK Fertilizer on The Growth And Yield of Long Beans (Vigna sinensis L.) Given Olf on Alluvial Soil - Bariyanto, Muhammad Deva; Rianto, Fadjar; Syahputra, Edy (Fakultas Pertanian Universitas Tanjungpura, 2025)
Green bean (Vigna sinensis L.) has the potential to be developed as a vegetable in Indonesia. Optimization of alluvial soil as a growing medium for green beans by providing organic and inorganic fertilizers. This study aims to determine the efficiency of using NPK granular compound fertilizers on green beans given Organic Liquid Fertilizer (OLF) in alluvial soil. This study took place from August to November 2024 using a Completely Randomized Design (CRD) with one factor. The treatments tested for NPK fertilizer doses consisted of 6 treatment levels, namely fertilizer doses of 150 kg/ha, 200 kg/ha, 250 kg/ha, 300 kg/ha, 350 kg/ha, and 400 kg/ha. All treatments sprayed by OLF, except for 400 kg/ha. The study was repeated 4 times and in each replication there were 3 sample plants. Green beans of the Kanton Tavi variety were planted in polybags. The variables observed were plant height (cm), number of branches, root volume (cm3), dry weight of plants (g), number of pods per plant (pod), length of pods (cm), fresh weight of pods per plant (g). The planting medium of each polybag was given lime so that the pH reached 6.17-6.64. The 2 mL/L OLF concentration was sprayed onto each plant every week until a week before be harvested. The results showed that NPK affected the variables of dry plant weight and fresh pod weight per plant. The application of NPK fertilizer at a dose of 350 kg/ha was the best dose for the growth and yield of green beans with the highest average value of fresh pod weight per plant of 220.55 g. Using OLF can save 37.5% of NPK fertilizer use on green beans.